Oxidation states and microstructure of manganese impurity centers in nanosized Al₂O₃ obtained by combustion method - Berezovskaya, I.V.; Khomenko, O.V.; Poletaev, N.I.; Khlebnikova, M.E.; Stoyanova, I.V.; Efryushina, N.P.; Dotsenko, V.P. (Functional Materials, 2018)
Nanosized (10-70 nm) Al₂O₃ doped with manganese ions (Mn³⁺) was obtained by combustion method. It was found that the resulting powder consists of a mixture of transition aluminas (δ*, δ, θ), among which δ*-phase is dominant. It was shown that a part of Mn ions exists in the oxidation state +2 and occupies tetrahedral positions in δ*-Al₂O₃, causing a broadband luminescence with a maximum at ~ 520 nm. Annealing in air at temperatures ≤1130 °C results in the formation of stable α-polymorph. It is shown that the δ*, θ -> α-Al₂O₃ phase transition is followed by oxidation of Mn²⁺/Mn³⁺ ions and the stabilization of some amount of manganese ions in the oxidation state +4 on octahedral Al positions.